2018
DOI: 10.1089/thy.2018.0022
|View full text |Cite
|
Sign up to set email alerts
|

Anlotinib for the Treatment of Patients with Locally Advanced or Metastatic Medullary Thyroid Cancer

Abstract: Anlotinib demonstrated a durable antitumor activity with a manageable adverse event profile in locally advanced or metastatic MTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 28 publications
2
86
0
Order By: Relevance
“…It is a novel multi-target TKI that is designed to primarily inhibit VEGFR2/3, FGFR1-4, PDGFR a/b, c-Kit, and Ret. In so-doing, it effectively suppresses tumor angiogenesis and growth, with acceptable toxicity as seen in lu ng squamous cell carcinoma, advanced lung adenocarcinoma, small cell lung cancer, soft tissue sarcoma, medullary thyroid cancer, and metastatic renal clear cell cancer (Han et al, 2018;Sun et al, 2018;Shao et al, 2019;Yang et al, 2019;Zhou et al, 2019). Its major side effects include fatigue, high blood pressure, hand-foot skin reaction, gastrointestinal reactions, triglyceride elevation cholesterol elevation, and blood thyrotrophin elevation (Sun et al, 2016;Shao et al, 2019;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is a novel multi-target TKI that is designed to primarily inhibit VEGFR2/3, FGFR1-4, PDGFR a/b, c-Kit, and Ret. In so-doing, it effectively suppresses tumor angiogenesis and growth, with acceptable toxicity as seen in lu ng squamous cell carcinoma, advanced lung adenocarcinoma, small cell lung cancer, soft tissue sarcoma, medullary thyroid cancer, and metastatic renal clear cell cancer (Han et al, 2018;Sun et al, 2018;Shao et al, 2019;Yang et al, 2019;Zhou et al, 2019). Its major side effects include fatigue, high blood pressure, hand-foot skin reaction, gastrointestinal reactions, triglyceride elevation cholesterol elevation, and blood thyrotrophin elevation (Sun et al, 2016;Shao et al, 2019;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Anlotinib has encouraging antitumor effects and acceptable toxicity in advanced lung adenocarcinoma, lung squamous cell carcinoma, STS, medullary thyroid cancer, small cell lung cancer and metastatic renal clear cell cancer. [15][16][17][18] A Phase II clinical trial showed that a total of 166 relapsed advanced STS patients had a significant survival benefit after treatment with anlotinib, with a 12-week progressionfree rate of 68.42% and an objective response rate of 12.65%. The PFS and OS were 5.63 and 12.33 months, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As a multitargeting tyrosine inhibitor in clinical development, Anlotinib exerts antitumor effects through anti-angiogenesis activity targeting multiple tyrosine kinases such as vascular endothelial growth factor receptor 1/2/3 (VEGFR-1/2/3), platelet-derived growth factor receptor (PDGFR) and broblast growth factor receptor (FGFR) [8]. It was reported that Anlotinib have signi cant antitumoral effect on solid tumor including thyroid cancer [9], non-small lung cancer [10], soft tissue sarcoma [11], renal cancer [12] and gastric cancer [13]. However, there is little research focusing on whether Anlotinib have an antitumor effect on oral squamous cell carcinoma which is one of the most common cancers in head and neck region.…”
Section: Discussionmentioning
confidence: 99%